Cold fusion ebook - Pendleton, Don (2013)
A deadly auction is about to take place as two scientists put their prototype for harnessing cold fusion on the market. Scheduled to be sold to the highest bidder in a secret Syrian location, the knowledge of how to harness cold fusion would give great and dangerous nuclear power to its owner. As Mack Bolan races to intercept the exchange, he discovers he's not the only one intent on crashing the bidding party. A group of Russians have hijacked the proceedings and disappeared with the scientists. The Russians expect an even higher price for the brains behind the scientific breakthrough, and Bolan must track the ex-KGB kidnappers across the desert from Syria to Libya and stop them from trading their human merchandise. Access to technology is low, so the Executioner will have to resort to WWII desert warfare strategies to put these Russians out of business—permanently.